2014
DOI: 10.1186/cc13952
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus bolus intermittent loop diuretic infusion in acutely decompensated heart failure: a prospective randomized trial

Abstract: IntroductionIntravenous loop diuretics are a cornerstone of therapy in acutely decompensated heart failure (ADHF). We sought to determine if there are any differences in clinical outcomes between intravenous bolus and continuous infusion of loop diuretics.MethodsSubjects with ADHF within 12 hours of hospital admission were randomly assigned to continuous infusion or twice daily bolus therapy with furosemide. There were three co-primary endpoints assessed from admission to discharge: the mean paired changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 34 publications
1
64
1
11
Order By: Relevance
“…32 Although these data do not support using continuous diuretic infusions for acute decompensated heart failure, several caveats should be mentioned. Continuous infusions were not routinely preceded by loading doses in the DOSE trial, which speed achievement of steady state.…”
Section: Introductionmentioning
confidence: 94%
“…32 Although these data do not support using continuous diuretic infusions for acute decompensated heart failure, several caveats should be mentioned. Continuous infusions were not routinely preceded by loading doses in the DOSE trial, which speed achievement of steady state.…”
Section: Introductionmentioning
confidence: 94%
“…Several recent randomised controlled trials (RCTs) have investigated the efficacy and safety profiles of modes of administration (continuous infusion vs. bolus) of i.v. furosemide in heart failure populations, but results have been conflicting . Continuous infusion of furosemide is believed to confer additional benefits over bolus injection, with less variability in peak plasma furosemide concentration resulting in a consistent, predictable urine output and less risk of electrolyte disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the largest multi‐centre RCT comparison, conducted by Felker et al found no significant difference in mortality and other clinical end‐points between continuous infusion or bolus injection of furosemide in heart failure. Several recent trials have suggested a higher incidence of potentially harmful effects with continuous infusions, namely transient hypotension, electrolyte disturbance and acute kidney injury . Thus, it remains unclear whether one method of furosemide administration is superior to the other in the heart failure population.…”
Section: Introductionmentioning
confidence: 99%
“…27 In contrast, our study showed that a significant BNP reduction during loop diuretic treatment was not associated with reduced mortality or rehospitalization in patients with both reduced and preserved renal function. 28,29 Different results in several studies could be influenced by several variables: they could ride on the hemodynamic picture and left ventricular filling pressure levels; they could depend on water and sodium overload entity as well as on different response to treatment. Finally, they could depend on baseline characteristic of patients enrolled: gender, body weight, presence of renal dysfunction and co-morbidities are all potential confounding factors.…”
Section: Discussionmentioning
confidence: 98%